The effect of Cooperative Learning Strategy on Sensory Modeling on the Performance of Some Essential Skills for Female Students’ Basketball - Zahraa Abdul-Jabbar Habib1 , Hassan Saleh Mahdi Al-Okbi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study aimed to identify the preference for sensory modelling among fifth-grade middle school studentsand to identify the impact of cooperative learning strategy according to the sensory preference for some basicskills in basketball among fifth-grade middle school students and identifies the current research communityof school students for the fifth middle school, the research sample was chosen in a way Random, as usingthis method means that each member of society has an equal opportunity to choose him in the sample. Thisresearch included the application and poll of (48) students (Al-Imam Al-Rida School, peace be upon him/ Basra). The researchers concluded that the cooperative learning strategy according to sensory modellingIts positive impact on teaching some skills for fifth-grade students preparatory for experimental groups inall tribal and post-tests, and the curriculum used by the teacher has a positive effect on teaching some ofthe skills capabilities of fifth-grade students preparatory for the group controlling in all pre and post-testsif to use a cooperative learning strategy according to modelling Sensory has positively affected some skillsof the experimental group as compared to the total The control group in the test had the least significantdifference for the experimental groups compared to the control group. The use of cooperative learningstrategy according to sensory modelling has provided more time that can be used to achieve the objectivesof the lesson without the critical time that can be used to correct and repeat more.